Legal Contours of Sustainable Development: Historical Tracker and Arguments Supporting Its Normativity - Korchahin, Dmytro (Teisė, 2024)
In the present paper the author overviews the historical tracking of sustainable development as such. Besides, in the article, the current legal nature of sustainable development and some aspects helping to enhance its legal contours are revealed. The concept of sustainable development has gradually evolved through different political forums and discussions. This process has been taking more than fifty years. The current legal contours of sustainable development are not stable, making scientists look for their proper outline. Therefore, the practice of the International Court of Justice (ICJ) is analysed, together with the EU (supranational) policymaking and the current state of environmental emergency. Based on the methods from the qualitative approach, the output on the legal contours of sustainable development and sustainability is proposed. Outside of the general formula of the obligation of states to act in a way that can guarantee sustainable development, some novel aspects of its enhanced regulatory value have been identified, bringing a new interpretation of the legal contours of sustainable development. These news aspects revolve around the realm of ambient reality (the current state of environmental emergency that dictates putting sustainable development at the centre of policymaking on different levels), the realm of ICJ case law (since the current case law is outdated, prospect advisory opinions of ICJ are needed to clear out the current legal contour of sustainable development), and the realm of supranational policymaking of the EU (in which sustainable development has become quite unstable but imperative, being at the heart of the factual policymaking).